PROBLEMS AND WAYS TO IMPROVE THE SIMPLIFIED TAXATION SYSTEM IN UKRAINE - Ponomareva, Tatiana; Hrynevich, Katerina (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2020)
The article considers such a problem of the modern tax system of the country as evasion of tax liabilities in full or in part by business entities. The general idea of creating a simplified taxation system in Ukraine is considered. The positive tendency to increase tax revenues in comparison with 2019 and 2020 is described. The data on the number of small business entities in Ukraine are given. The most common methods of tax evasion are analyzed and the possible effect of tax evasion of taxpayers is analyzed in full of their obligations to pay the budget, and as a result, such actions of economic entities are assessed. Steps to improve this system of taxation by the state authorities, through the mandatory maintenance of registrars of settlement operations (RRO) and the abolition of the Books of income (and expenses) for a simplified system of taxation are considered. The focus is on the mandatory conduct of RRO for a simplified system and substantiates the emergence of possible small business waste in the "shadow", in order to keep the company at a decent competitive level. The conduct of penalties for non-use of RRO in its activities is generalized. The idea of abolishing the Accounting Books and the imperfection of the law for newly established enterprises was also considered. The legally established fact of transition to full electronic correspondence of business entities and representatives of controlling bodies is described. It is determined that the transition to electronic documentation is a good thing for the state to reduce bureaucracy in the country. An example of the fight against the shadow economy in the United States is given. The article suggests the ways to improve the tax system of Ukraine using the experience of foreign countries.